Labour institutions and the regulation approach:The Malaysian case. - Wangel, Arne
Malaysia's rapid economic growth, industrial development and state policies is subject for numerous studies emphasising, among other. things, the expansion of certain industries, structural barriers on the labour market, accumulation of local (manufacturing) capital, establishment of resource-based industries, state-participation in manufacturing activities and the ethnic configuration of social forces.